REFUGEE AND LAND DISPUTE (A Case Study at Gamsungi and Tosoa Villages, South Ibu District, Regency of West Halmahera, Year 2015) - La Suhu, Bakri; Wance, Marno; Hasan, Ikram (Universitas Muhammadiyah Yogyakarta, 2019)
This study aims at figuring out the causes of land disputes and the settlement between Gamsungi and Tosoa villagers in South Ibu District of West Halmahera Regency. This study applies qualitative descriptive method in which it is a series of procedures used in solving the problems being investigated by describing the state of research objects at present time based on existing facts. The data sources used are primary and secondary data. While the technique of data collections are observation, document interview and secondary data aid. The results show that the causes of land dispute between Gamsungi and Tosoa villages due to: a). The arrival of ex-refugees from Lata-lata village in South Halmahera regency, b). Land expropriation and/ or land disposal by ex-refugees of Lata-lata village to the agricultural field of Gamsungi villagers, and c). Felling of plants in the agricultural field of Gamsungi villagers done by Lata-lata refugees. Therefore, the mechanism or way of settling land disputes between these two villages is through negotiation (consensus). Negotiations were done between the two villages’ representatives (Gamsungi and Tosoa villages): the two villages’ heads, secretaries, customary figures, religious leaders, and heads of BPD, and witnessed by Subdistric Head of South Ibu, Head of Criminal Investigation Unit of West Halmahera, Representatives of West Halmahera Government, Police Chief of Ibu, Sambung Rasa Team, and Koramil of Ibu.